(untitled) (Journal of Comparative & International Higher Education, 2024)
Critical thinking is an important part of higher education in Canada, and many education systems worldwide, but not all cultural contexts. Critical thinking enables students to expand their perspectives and better navigate important personal and professional decisions. This narrative inquiry compares Canadian and Iranian international graduate students’ perceptions of critical thinking. Through conversations with eight participants, deep and complex transcultural understandings of critical thinking were unearthed. Findings indicate that while Canadian participants can articulate informed viewpoints about critical thinking, some Iranian participants require further knowledge to construct their critical thinking conceptualizations. Results suggest that Canadian higher education needs to consider international students’ limited background knowledge of critical thinking and must provide more opportunities to develop critical thinking skills. This study offers insights for higher education policymakers, curriculum developers, and practitioners to consider international and intercultural perspectives to facilitate critical thinking in both international and domestic students.